Important humanistic values in the formation of the medical professional: what students and teachers think (Research, Society and Development, 2022)
The objective of this study is to know the humanistic values, considered by medical students and professors, as important in the education of students. Descriptive cross-sectional study. The population included 203 students and 69 professors from the medical course at a private university in Fortaleza. Data collection was performed using a questionnaire using Google Forms ®️. The study was approved by the local Ethics Committee. The informed consent was completed and signed by participants. The average age among students was 21.9 ± 4.4 years, and among professors, it was 49.2 ± 11.3 years. Most of the evaluated individuals were female. Among the students, a total of 924 humanistic values were counted. The fifteen values with the highest citation frequency were grouped in a word cloud. About 20.1% of the total was represented by the concept “empathy”, followed by “respect” with 14.2% and “humility” with 7.9%. In the teachers' evaluation, “empathy” (16%) was the most cited value, followed by “ethics” (11.7%) and “respect” (9%). Values such as “compassion”, “honesty”, “resilience'' and “dedication” were mentioned in a balanced way by both groups. Empathy was the most cited human value, both by students and teachers, followed by respect, ethics and humility. Values such as compassion, honesty, resilience were also important. These values must be encouraged throughout the medical course.